Sustainable Development Integrated in the Concept of Resilence - Bloesch, Jürg; von Hauff, Michael; Mainzer, Klaus; Mohan, S. Venkata; Renn, Ortwin; Risse, Verena; Song, Yonghui; Takeuchi, Kazuhiko; Wilderer, Peter A. (Problemy Ekorozwoju, 2015)
The purpose of sustainable development is to minimize the likelihood of dynamic natural and/or man-made systems to exceed tipping points, when exposed to disturbances. In effect, the systems are protected from losing identity and integrity. The authors of this paper suggest accepting resilience thinking as a basis of setting sustainability goals and reaching the respective targets. The resilience theory provides the method needed to maintain identity and integrity, and to manage system´s dynamics. Of concern are three interwoven systems: environment, society and economy, forming a complex super-system coined eco-social triad. Sustainable development of the triad applies to each of the three sub-systems despite conflicting interests of the various actors within each. Resilience is expressed by the ability of natural or man-made systems to respond dynamically to changes of ambient conditions with the aim to retain their inherent function, structure and feedbacks. To manage such changes and associated disturbances a repetitive sequence of processes (also called adaptive cycle) needs to be executed. In ecosystems these cycles are self-regulated and characterized by recycling of materials and energy. In systems dominated by humans adaptive cycles are characterized by phases such as re-evaluation, re-orientation and re-commencement. The concept of adaptive cycles and adaptive management embedded in the resilience theory is considered a promising method to satisfy sustainability goals and reach respective targets.